Hydrometeorological droughts in the Miño–Limia–Sil hydrographic demarcation (northwestern Iberian Peninsula): the role of atmospheric drivers - R. Sorí; M. Vázquez; M. Stojanovic; R. Nieto; M. L. R. Liberato; L. Gimeno (Natural Hazards and Earth System Sciences, 2020)
Drought is one of the world's primary natural hazards because of its environmental, economic, and social impacts. Therefore, monitoring and prediction for small regions, countries, or whole continents are challenging. In this work, the meteorological droughts affecting the Miño–Limia–Sil hydrographic demarcation in the northwestern Iberian Peninsula during the period of 1980–2017 were identified. For this purpose and to assess the combined effects of temperature and precipitation on drought conditions, the 1-month standardized precipitation evapotranspiration index (SPEI1) was utilized. Some of the most severe episodes occurred during June 2016–January 2017, September 2011–March 2012, and December 2014–August 2015. An empirical-orthogonal-function analysis revealed that the spatial variability of the SPEI1 shows strong homogeneity in the region, and the drought phenomenon consequently behaves in the same way. Particular emphasis was given to investigating atmospheric circulation as a driver of different drought conditions. To this aim, a daily weather type classification based on the Lamb weather type (LWT) classification was utilized for the entire Iberian Peninsula. Results showed that atmospheric circulation from the southwest, west, and northwest are directly related to wet conditions in the Miño–Limia–Sil hydrographic demarcation during the entire hydrological year. Contrastingly, weather types imposing atmospheric circulation from the northeast, east, and southeast are best associated with dry conditions. Anomalies of the integrated vertical flow of humidity and their divergence for the onset, peak, and termination of the 10 most severe drought episodes also confirmed these results. In this sense, the major atmospheric teleconnection patterns related to dry and wet conditions were the Arctic Oscillation, Scandinavian pattern, and North Atlantic Oscillation. Hydrological drought investigated through the standardized runoff index was closely related to dry and wet conditions revealed by the SPEI at shorter ...